Restorative Justice sebagai Solusi Alternatif: Analisis Efektivitas dalam Penanganan Tindak Pidana Anak di Indonesia - Aan Supriyadi; Yuyut Prayuti (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the effectiveness of implementing Restorative Justice (RJ), particularly through the Diversion mechanism, in addressing juvenile crimes in Indonesia, based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA). Restorative Justice demonstrates high effectiveness in achieving its main objectives, namely realizing justice oriented towards restoration and ensuring the best interests of the child, by reducing the risk of stigmatization and criminalization. This study aims to examine in depth the Effectiveness of Implementing Restorative Justice in the Resolution of Juvenile Crimes in Indonesia and the Implementation of Restorative Justice through Fulfilling Restitution for Victims of Juvenile Crimes. This research employs a normative juridical methodology, which involves the analysis and examination of secondary data. The research conducted by the author in relation to a normative juridical approach uses a literature review. Although the Child Protection and Juvenile Justice Law (UU SPPA) has provided a modern and humanistic legal framework, its implementation faces significant challenges. The success of restorative justice and the fulfillment of restitution heavily depends on the readiness of infrastructure (especially the Correctional Centers/Bapas), the improvement of facilitator quality, and a change in mindset of all stakeholders (officials and the community) to support solutions focused on recovery rather than retribution.